[Qué + Swear Word] as an Intensifying Comment of an Assertion - Fuentes Rodríguez, Catalina (2023)
The construction [qué + swear word] appears in different discursive contexts. It can act as an independent statement, as a complex interjective variant, in reactive interventions, or is integrated within an utterance, occupying peripheral positions. In the latter context, it develops procedural contents similar to those of discourse markers: specifically, it develops a meaning of reformulation and another one of reconsideration, in which it adds an argumentative counterorientation to what is expected by the listener. This paper analyses its functions from a linguistic-pragmatic perspective which takes into account the macrosyntactic functions of the construction.